Thermo-economic analysis and multi-objective optimization of a renewable-based integrated energy system with hydrogen production and LNG utilization in South Africa - Zhuo Yang; Wenting Xu; Yue Gao; Fanhua Rong; Changnian Chen; Tien-Chien Jen; Zeting Yu (Fuel, 2026)

A natural Nlscarlet insertion underlies the orange-eye phenotype and facilitates efficient multiple-sgRNA genome editing in Nilaparvata lugens - Wen-Nan Ye; Rong-Yu Chen; Qi Xing; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Insect Biochemistry and Molecular Biology, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Regulatory role of the keystone taxa Dokdonella in bacterial network stability under grazing disturbance in alpine meadows - Hainian Lu; Jiaoyang Du; Yongli Xie; Yu Zou; Xiujin Zhang; Dingan Gao; Xiaohui Wu; Chaokun Wang; Rong Wang (Rhizosphere, 2026)

Field resistance monitoring and nAChR α6 target validation support spinetoram as a candidate insecticide for rotation in Nilaparvata lugens resistance management - Wen-Nan Ye; Qi Xing; Rong-Yu Chen; Yan-Chao Zhang; Shun-Fan Wu; Cong-Fen Gao (Pesticide Biochemistry and Physiology, 2026)

Additives-induced alteration of PVC pyrolysis pathways and emission profiles - Siying Ran; Haoran Yu; Rong Cao; Ningbo Geng; Yuan Gao; Haijun Zhang; Lidong Wu; Jiping Chen (Journal of Hazardous Materials, 2026)

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Partitioned identification of vegetation drivers and their interactions in the Loess Plateau via interpretable XGBoost-SHAP - Yi Ren; Jia Tian; Xuejuan Feng; Guowei Wu; Caifeng He; Wei Bao; Tao Yu; Jiahui Gao; Tao Wang; Jian Wen; Rong Tao (Environment, Development and Sustainability, 2026)

Extracellular polymeric substances: overlooked contributors to soil organic carbon persistence - Yichao Wu; Yuwei Yi; Minsu Kim; Samuel Bickel; Ming Zhang; Ke Dai; Chunhui Gao; Chenchen Qu; Chuisi Kong; Mengxi Feng; Ke-Qing Xiao; Hans-Curt Flemming; et al. (Soil Biology and Biochemistry, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Modelling the corrosion process of reinforced concrete structure in marine atmosphere zone considering chloride aerosol deposition and carbonation - Le-rong Wang; Liang-yu Tong; Pan-yue Gao; Yi-fei Chen; Qing-xiang Xiong; Qing-feng Liu (Ocean Engineering, 2026)

Metabolic rewiring of Phanerochaete chrysosporium to enhance tolerance and degradation of aged polystyrene microplastics: Pyruvate metabolism and actin polarization - Yongkang Wu; Zelin Hou; Yin Lu; Rong Cai; Jiawei Huang; Yu Mao; Ningjia Dong; Hong Liang; Dawen Gao (Journal of Hazardous Materials, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Chemical speciation and structure of lithium (Li) in coal gasification fine slag: Evolution mechanisms and implications for Li recovery - Biao Fu; Xia Wu; Chengxiang Yu; Xinru Zhou; Hongyan Nan; Yijun Cao; Yukun Huang; Yuhang Gao; Guangqing Hu; Zhongjie Shen; Lingkun Rong (Fuel, 2026)

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

Formation, Potential, and Challenges of Marine-Continental Transitional Shale Gas in China - Caineng Zou; Dazhong Dong; Qin Zhang; Weiliang Kong; Wen Liu; Zhenyu Zhao; Zhi Yang; Qun Zhao; Rong Ding; Guangyin Cai; Tianquan Qu; Wanli Gao; et al. (Journal of Earth Science, 2026)

A deep learning-based prognostic approach for predicting PWR degradation and remaining useful life using GNN-PTC-LSTM - Shadman Ahmad Khattak; Liu Yong-Kuo; Liu Yu-Kun; Gao Jia-Rong; Shi Zhou-Xin; Liu Ji (Annals of Nuclear Energy, 2026)

Efficient Co-hydrothermal conversion of corn straw and pig manure into nitrogen-enriched soluble humic acid fertilizer - Weizhong Huo; Zhaofan Lin; Feng Gao; Jing Yu; Xutong Pang; Rong Ye; Yuchao Shao; Youzhi Miao; Qirong Shen; Ruifu Zhang (Journal of Environmental Management, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Chemical constituents from the twigs and leaves of Viburnum utile Hemsl. (Adoxaceae) and their taxonomic distribution - Dong-Mei Zhou; Lijin Jiao; Huai-Qin Liu; Bang-Quan Tang; Guo-Bo Xu; Qin-Feng Zhu; Xi-Rong Luo; Shang-Gao Liao; Ling-Ling Yu (Biochemical Systematics and Ecology, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

High-purity quartz sand from mineral purification: a review on process, mechanism, and environmental strategies - Zhongxiang Yu; Dawei Luo; Ke Zhao; Ke Rong; Jiabao Deng; Zijie Gao (Minerals Engineering, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Taxonomy and phylogeny of Erysiphe species on Liquidambar formosana (Hamamelidaceae) - Jing Feng; Shuang-Bao Wang; Shu-Yan Liu; Michael Bradshaw; Uwe Braun; Shou-Rong Yu; Guan-Xiu Guan; Dan-Ni Jin; Zhao-Yang Zhang; Han-Xing Gao (New Zealand Journal of Botany, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Advances in acetylcholinesterase-based biosensing technologies for organophosphorus pesticide detection: A comprehensive review (2020–2024) - Qian Zhang; Jing Yu; Yanping Wei; Rong Yang; Jin Liu; Yangyang Su; Die Gao; Jing Zeng (Food Chemistry, 2025)

Application of modified biochar in constructed wetlands for efficient livestock wastewater treatment - Tong Xu; Rong Gao; Yu Yan; Jun Fang; Sujuan Ding (Environmental Research, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Identification of the Dirigent Genes in Arctium lappa and their Relevance to the Stress Response - Mingze Gao; Ying Yu; Jianing Xue; Yilin Han; Rong Zhao (Plant Molecular Biology Reporter, 2025)

Upregulation of NR2A in Glutamatergic VTA Neurons Contributes to Chronic Visceral Pain in Male Mice - Meng-Ge Li; Shu-Ting Qu; Yang Yu; Zhenhua Xu; Fu-Chao Zhang; Yong-Chang Li; Rong Gao; Guang-Yin Xu (Neuroscience Bulletin, 2025)
Chronic visceral pain is a persistent and debilitating condition arising from dysfunction or sensitization of the visceral organs and their associated nervous pathways. Increasing evidence suggests that imbalances in central nervous system function play an essential role in the progression of visceral pain, but the exact mechanisms underlying the neural circuitry and molecular targets remain largely unexplored. In the present study, the ventral tegmental area (VTA) was shown to mediate visceral pain in mice. Visceral pain stimulation increased c-Fos expression and Ca 2+ activity of glutamatergic VTA neurons, and optogenetic modulation of glutamatergic VTA neurons altered visceral pain. In particular, the upregulation of NMDA receptor 2A (NR2A) subunits within the VTA resulted in visceral pain in mice. Administration of a selective NR2A inhibitor decreased the number of visceral pain-induced c-Fos positive neurons and attenuated visceral pain. Pharmacology combined with chemogenetics further demonstrated that glutamatergic VTA neurons regulated visceral pain behaviors based on NR2A. In summary, our findings demonstrated that the upregulation of NR2A in glutamatergic VTA neurons plays a critical role in visceral pain. These insights provide a foundation for further comprehension of the neural circuits and molecular targets involved in chronic visceral pain and may pave the way for targeted therapies in chronic visceral pain.

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

Competent expression of effective and long-acting human α-Gal A-Fc fusion protein in the milk of transgenic mice - Mengke Yuan; Lan Yang; Chunyang Li; Zhiqiang Wu; Zhipeng Liu; Tianfei Du; Xinzong Rong; Cong Cong; Yongxia Zhang; Xiaoping Yu; Yali Gao; Zhengli Chen; et al. (Transgenic Research, 2025)

The dynamic succession of the core microbial communities in pasteurized milk during refrigeration based on metagenomics - Chunyan Hu; Rong Guo; Jiao Zhuang; Yan Gao; Xia Zhang; Yu Meng; Zhen Liu; Yongxia Bian; Liqing Wu; Shuai Guo; Ning Ju (International Dairy Journal, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

Decoupled motion planning method for 7-DOF manipulator and lifting joint in automated tomato harvesting - Jiacheng Rong; Yu Liu; Xianjun Li; Chao Gao; Pengbo Wang; Ting Yuan; Wei Li (Computers and Electronics in Agriculture, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Oxygen vacancies-mediated the peracetic acid activation to selectively generate 1O2 for water decontamination - Yi Chen; Qian Li; Ruidian Su; Yixuan Gao; Ning An; Yu Rong; Xing Xu; Defang Ma; Yan Wang; Baoyu Gao (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

A hybrid coupled model for the tropical Pacific constructed by integrating ROMS with a statistical atmospheric model - Rong-Hua Zhang; Wenzhe Zhang; Yang Yu; Yinnan Li; Feng Tian; Chuan Gao; Hongna Wang (Journal of Oceanology and Limnology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Synthetic phenolic antioxidant contamination in farmland soils induced by mulching films: Distribution and transformation pathways - Shanxing Wu; Meng Gao; Bo Fang; Lili Rong; Zhanpeng Ge; Hao Chen; Yiming Yao; Yu Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Enhanced microbial degradation of hexabromocyclododecane in riparian sediments through regulating flooding regimes - Juan Chen; Rong Wang; Chao Wang; Peifang Wang; Han Gao; Yu Hu; Qihao Nie; Shunqing Zhang (Journal of Hazardous Materials, 2025)

Identification of the chemical composition of blue honeyberry leaves (Lonicera caerulea L. var. edulis) and their anti-inflammatory activity - Zhenji Rong; Chunping Yu; Xin Wang; Ruyue Wang; Yang Gao; Hailong Zhang (Medicinal Chemistry Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Precipitation patterns strongly affect vertical migration and methylation of mercury in legacy contaminated sites - Xujun Liang; Zhi-Cheng Hu; Yu-Rong Liu; Cunbin Gao; Yi Zhang; Yun-Yun Hao; Lijie Zhang; Jiating Zhao; Lizhong Zhu (Water Research, 2024)

Research advances in technologies and mechanisms to regulate vinegar flavor - Zhankai Zhang; Zhi-hong Zhang; Ronghai He; Guozhong Zhao; Yongjian Yu; Rong Zhang; Xianli Gao (Food Chemistry, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Co-culture of natural killer cells and tumor spheroids on a heterogeneous multilayer paper stack - Yuanyuan Xie; Xiaoyan Yang; Rong Pan; Lixia Gao; Ling Yu (Journal of Zhejiang University-SCIENCE B, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

Representing ocean biology-induced heating effects in ROMS-based simulations for the Indo-Pacific Ocean - Wenzhe Zhang; Chuan Gao; Feng Tian; Yang Yu; Hongna Wang; Rong-Hua Zhang (Frontiers in Marine Science, 2024)
Incident shortwave radiation can penetrate and heat the upper ocean water column, acting to modulate the stratification, vertical mixing and sea surface temperature. As a light-absorbing constituent, ocean chlorophyll (CHL) plays an important role in regulating these processes; however, its heating effect on the ocean state remains controversial and exhibits strong model dependence on ways the solar radiation transmission and the related CHL-induced heating are represented. In this study, we implement a chlorophyll-based two-way coupling between physical and ecological processes within the Regional Ocean Modeling System (ROMS). The bio-physics coupled model performs well in simulating the structure and variability of oceanic physical and ecological fields in the tropical Indo-Pacific region. Three CHL-related heating terms are analyzed based on the model output to diagnose the ocean biology-induced heating effects, namely the shortwave radiation part penetrating out of the base of the mixed layer (ML; Q pen ), the portion absorbed within the ML ( Q abs ), and the rate of temperature change of the ML resulting from the Q abs effects ( R sr ). Results show that the spatio-temporal distributions of the three heating terms are mainly determined by the ML depth (MLD). However, Q pen can also be regulated by the euphotic depth (ED), especially in the western-central equatorial Pacific. This moderating effect is particularly evident during El Niño when the ED tends to be greater than the MLD; positive ED anomalies act to enhance the positive Q pen anomalies caused by negative MLD anomalies. For the first time, the bio-heating effects are quantified within the ROMS-based two-way coupling context between the physical submodel and ecological submodel over the tropical Indo-Pacific Ocean, providing a basis for further understanding of the bio-effects and mechanisms. It is expected that the methodology and understanding developed in this study can help explore the chlorophyll-related processes in the ocean and the interactions with the atmosphere.

Enhancing effect of conductive materials and rumen microorganisms on the anaerobic digestion performance of a real traditional Chinese medicine wastewater - Han Gao; Xiang-Lin Chang; Su Li; Rong Chen; Yu-You Li; Bao-Shan Xing (Journal of Water Process Engineering, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Improved YOLOv8n for Lightweight Ship Detection - Zhiguang Gao; Xiaoyan Yu; Xianwei Rong; Wenqi Wang (Journal of Marine Science and Engineering, 2024)
Automatic ship detection is a crucial task within the domain of maritime transportation management. With the progressive success of convolutional neural networks (CNNs), a number of advanced CNN models have been presented in order to detect ships. Although these detection models have achieved marked performance, several undesired results may occur under complex maritime conditions, such as missed detections, false positives, and low detection accuracy. Moreover, the existing detection models endure large number of parameters and heavy computation cost. To deal with these problems, we suggest a lightweight ship model of detection called DSSM–LightNet based upon the improved YOLOv8n. First, we introduce a lightweight Dual Convolutional (DualConv) into the model to lower both the number of parameters and the computational complexity. The principle is that DualConv combines two types of convolution kernels, 3x3 and 1x1, and utilizes group convolution techniques to effectively reduce computational costs while processing the same input feature map channels. Second, we propose a Slim-neck structure in the neck network, which introduces GSConv and VoVGSCSP modules to construct an efficient feature-fusion layer. This fusion strategy helps the model better capture the features of targets of different sizes. Meanwhile, a spatially enhanced attention module (SEAM) is leveraged to integrate with a Feature Pyramid Network (FPN) and the Slim-neck to achieve simple yet effective feature extraction, minimizing information loss during feature fusion. CIoU may not accurately reflect the relative positional relationship between bounding boxes in some complex scenarios. In contrast, MPDIoU can provide more accurate positional information in bounding-box regression by directly minimizing point distance and considering comprehensive loss. Therefore, we utilize the minimum point distance IoU (MPDIoU) rather than the Complete Intersection over Union (CIoU) Loss to further enhance the detection precision of the suggested model. Comprehensive tests carried out on the publicly accessible SeaShips dataset have demonstrated that our model greatly exceeds other algorithms in relation to their detection accuracy and efficiency, while reserving its lightweight nature.

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Investigation on formation and combustion process of carbon deposits from coke oven riser during waste heat recovery - Yaqiang Yuan; Tao Rong; Huafang Yu; Hao Guo; Yan Gao; Jingsong Wang; Qingguo Xue; Haibin Zuo (Fuel, 2024)

Trade-offs of reproductive growth and Cd remobilization regulated Cd accumulation in wheat grains (Triticum aestivum L.) - Ying Wang; Pei-Pei Gao; Yu-Meng Shang; Rong-Rong Jia; Yu-Cheng Wang; Xiang-Yu Li; Li-Ping Geng; Yong Zhao; Joshua Walrath; Wen-Ju Liu (Journal of Hazardous Materials, 2024)

Application of coalbed methane assisted iron ore sintering: Injection effect, pollutant abatement and economic evaluation - Yaqiang Yuan; Tao Rong; Huafang Yu; Haibin Zuo; Hao Guo; Yan Gao; Jingsong Wang; Qingguo Xue (Journal of Cleaner Production, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

A systematic review of biochar aging and the potential eco-environmental risk in heavy metal contaminated soil - Xin-Xian Long; Ze-Ning Yu; Shao-wen Liu; Ting Gao; Rong-Liang Qiu (Journal of Hazardous Materials, 2024)

The conversion of monolignans to sesquilignans and dilignans is closely correlated to the regulation of Arctium lappa seed germination - Rong Zhao; Ying Yu; Mingze Gao; Yanping Xing; Jianing Xue; Liang Xu; Tingguo Kang (Planta, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Repeated labile carbon inputs trigger soil microbial necromass decomposition through increasing microbial diversity and hierarchical interactions - Xinyi Peng; Shenghan Gao; Silin Ma; Hao Liao; Yu-Rong Liu; Wenli Chen; Qiaoyun Huang; Xiuli Hao (Soil Biology and Biochemistry, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Integrating a heatscape index and a Patch CA model to predict land surface temperature under multiple scenarios of landscape composition and configuration - Jianxin Yang; Linxin Bao; Si Dong; Yuying Qiu; Jing Gao; Shisi Zou; Rong Tao; Xinzhu Fan; Xinyuan Yu (Sustainable Cities and Society, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

An airflow-driven system for scalable production of nano-microfiber wrapped triboelectric yarns for wearable applications - Yu Chen; Jie Hua; Yali Ling; Yang Liu; Mingtai Chen; Beomjun Ju; Wei Gao; Amanda Mills; Xiaoming Tao; Rong Yin (Chemical Engineering Journal, 2023)

Associations of exposure to bisphenol A and its substitutes with neurodevelopmental outcomes among infants at 12 months of age: A cross-sectional study - Zhuanning Xia; Cheng Lv; Yan Zhang; Rong Shi; Qi Lu; Ying Tian; Xiaoning Lei; Yu Gao (Chemosphere, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Nitrogen removal performance and bacterial flora analysis of a nitrification‑sulphur autotrophic denitrification coupled with permeable reaction wall (NSAD+PRW) treating rare earth mine groundwater - Shiqi Wang; Bai Gao; Shengfeng Liu; Nan Chen; Wenjie Ma; Rong Wang; Junzhe Wu; Yanling Yu (Journal of Water Process Engineering, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

Effects of nano-silicon dioxide on minerals, antioxidant enzymes, and growth in bitter gourd seedlings under cadmium stress - Hongyan Sun; Bo Zhang; Zhijiang Rong; Songjie He; Yifan Gao; Jia Yu; Qingmei Zhang (Acta Physiologiae Plantarum, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

New insights into sulfur input induced methylmercury production and accumulation in paddy soil and rice - Yunyun Li; Nali Zhu; Wenjun Hu; Yu-rong Liu; Wen Jia; Guoming Lin; Hong Li; Yufeng Li; Yuxi Gao; Jiating Zhao (Journal of Hazardous Materials, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Urban particulate water-soluble organic matter in winter: Size-resolved molecular characterization, role of the S-containing compounds on haze formation - Cuiping Ning; Yuan Gao; Haijun Zhang; Haoran Yu; Rong Cao; Jiping Chen (Science of The Total Environment, 2023)

Urinary neonicotinoid insecticides and adiposity measures among 7-year-old children in northern China: A cross-sectional study - Zhenping Lu; Yi Hu; Lap Ah Tse; Jinxia Yu; Zhuanning Xia; Xiaoning Lei; Yan Zhang; Rong Shi; Ying Tian; Yu Gao (International Journal of Hygiene and Environmental Health, 2023)

Diversity and interaction of bacterial and microeukaryotic communities in sediments planted with different submerged macrophytes: Responses to decabromodiphenyl ether - Han Gao; Juan Chen; Chao Wang; Peifang Wang; Rong Wang; Yu Hu; Ying Pan (Chemosphere, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Amendments of nitrogen and sulfur mitigate carbon-promoting effect on microbial mercury methylation in paddy soils - Yunyun Li; Shu-Shen Dai; Jiating Zhao; Zhi-Cheng Hu; Qin Liu; Jiao Feng; Qiaoyun Huang; Yuxi Gao; Yu-Rong Liu (Journal of Hazardous Materials, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Increases in temperature response to CO2 emissions in biochar-amended vegetable field soil - Rong Huang; Zifang Wang; Yi Xiao; Luo Yu; Xuesong Gao; Changquan Wang; Bing Li; Qi Tao; Qiang Xu; Ming Gao (Environmental Science and Pollution Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Circulatory and Metabolic Physiology Disorder in Different Organs of the Subtropical Scallop Species Chlamys nobilis Under Thermal and Hypoxia Stress, Revealed by Doppler Ultrasonography Technique - Yu Hao; Chunyang Sun; Yun Rong; Haiqing Wang; Qiang Xu; Fei Gao; Aimin Wang (Frontiers in Marine Science, 2022)
Extremely high temperature and hypoxia are mounting problems affecting the world’s coastal waters under the global warming environment, with severe consequences for marine life. Scallop is one of the most fragile species to hypoxia stress for their high respiration rate and lack of self-protection ability such as long-time shell closing. Circulatory physiology rhythm is sensitive to environmental stress and is an important means for shellfish to quickly respond to environmental stress. Therefore, monitoring the circulatory physiology indexes of Chlamys nobilis under hypoxia and high temperature stress is helpful to quickly diagnose its stress state and reveal the response process of circulatory system to the stress. In this study, using real-time Doppler ultrasonography technique, we continuously monitored the circulatory physiological indexes [heart rate (HR), blood flow volume (FV), blood velocity (PS and ED), resistance index (RI) and S/D ratio) of the scallop organs (gill, mantle and adductor muscle) under hypoxia (mild 4 mg/L DO, moderate 3 mg/L DO and severe 2 mg/L DO)] and fluctuating high temperature stress (29-31°C). Important metabolic function indexes [adenosine triphosphate (ATP), pyruvate kinase (PK) and cytochrome C oxidase (COX)] of various tissues were measured simultaneously. The results show that scallops are very sensitive to the changes of temperature and dissolved oxygen. Both high temperature and hypoxia will increase the HR, and severe hypoxia will bring greater load to the heart of the scallop. Hypoxia stress mainly caused the changes of PS, and the RI and S/D of the gill gradually increased. At 2mg/L DO level, the total blood flow of the mantle and adductor muscle decreased, but the blood flow supply in the gill was stable. The scallop is very sensitive to the change of high temperature and can make adjustments immediately. High temperature increased blood flow in various organs and preferentially supplied to the gill. The RI and S/D of branchial vessels under high temperature were lower than those under hypoxia. The ATP content of the mantle was continuous accumulated under high temperature and was significantly higher than that of the gill and adductor muscle, indicating the specificity of tissue metabolism. The overall circulatory physiological indexes of the gill showed a more positive response to the stress environment than the mantle and adductor muscle. All the results proved that the gill has the best resistance to the hypoxia and high temperature stress. Our study revealed the circulatory physiology regulation mechanism of the noble scallop C. nobilis under environmental stress, and provide effective data and technique supports for the timely diagnose of stress condition of the species, so as to formulate necessary handling strategies for the scallop farm.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

On the Second-Year Warming in Late 2019 over the Tropical Pacific and Its Attribution to an Indian Ocean Dipole Event - Licheng Feng; Fei Liu; Rong-Hua Zhang; Xue Han; Bo Yu; Chuan Gao (Advances in Atmospheric Sciences, 2021)

Activation of the Hippocampal LXRβ Improves Sleep-Deprived Cognitive Impairment by Inhibiting Neuroinflammation - Chen Qiu; Min Wang; Wen Yu; Zheng Rong; He-Sheng Zheng; Ting Sun; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2021)

A new atypical short‐chain dehydrogenase is required for interfungal combat and conidiation in Trichoderma guizhouense - Hong Zhu; Jian Zhang; Qi Gao; Guan Pang; Tingting Sun; Rong Li; Zhenzhong Yu; Qirong Shen (Environmental Microbiology, 2021)
Summary Hypocrealean Trichoderma are the most extensively studied facultative mycoparasites against phytopathogenic fungi. Aerial hyphae of Trichoderma guizhouense can rapidly proliferate over Fusarium oxysporum hyphae, cause sporadic cell death and arrest the growth of the host. The results of the present study demonstrated that a unique short‐chain dehydrogenase/reductase (SDR), designated as TgSDR1, was expressed at a high level in T . guizhouense challenged by the hosts. Similar to other SDRs family members, the TgSDR1 protein contains a cofactor‐binding motif and a catalytic site. The subcellular localization assay revealed that the TgSDR1::GFP fusion protein translocated to lipid droplets in mycelia and conidia. The data obtained using reverse genetic approach indicated that TgSDR1 is associated with antifungal ability, plays an important role in providing reducing equivalents in the form of NADPH and regulates the amino sugar and nucleotide sugar metabolism in T . guizhouense upon encountering a host. Moreover, the TgSDR1 deletion mutant was defective in conidiation. Thus, TgSDR1 functions as a key metabolic enzyme in T . guizhouense to regulate mycotrophic interactions, defence against other fungi, such as F . oxysporum , and conidiation.

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Growth influence of juvenile golden trout (Oncorhynchus mykiss) in different osmotic conditions: implications for tissue histology, biochemical indicators, and genes transcription involved in GH/IGF system - Baoliang Bi; Yu Gao; Dan Jia; Lingfu Kong; Yanhua Su; Hua Rong; Xiangwei Wu; Xiaowen Wang; Zhuoyong Hu; Qing Hu (Fish Physiology and Biochemistry, 2021)

Antidepressant Effect of Paeoniflorin Is Through Inhibiting Pyroptosis CASP-11/GSDMD Pathway - Dan-Dan Tian; Min Wang; An Liu; Mei-Rong Gao; Chen Qiu; Wen Yu; Wen-Ju Wang; Kun Zhang; Le Yang; Yan-Yan Jia; Chang-Bin Yang; Yu-Mei Wu (Molecular Neurobiology, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Prenatal diagnosis and neonatal phenotype of a de novo microdeletion of 17p11.2p12 associated with Smith‒Magenis syndrome and external genital defects - Pingping Zhang; Yanmei Sun; Haishen Tian; Limin Rong; Fangna Wang; Xiaoping Yu; Yali Li; Jian Gao (Journal of Genetics, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

A review of progress in coupled ocean-atmosphere model developments for ENSO studies in China - Rong-Hua Zhang; Yongqiang Yu; Zhenya Song; Hong-Li Ren; Youmin Tang; Fangli Qiao; Tongwen Wu; Chuan Gao; Junya Hu; Feng Tian; Yuchao Zhu; Lin Chen; et al. (Journal of Oceanology and Limnology, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Effect of different seasons (spring vs summer) on the microbiota diversity in the feces of dairy cows - Han Li; Rong Li; Huijun Chen; Jing Gao; Yu Wang; Yifeng Zhang; Zhili Qi (International Journal of Biometeorology, 2020)

Exposure to triclosan among pregnant women in northern China: urinary concentrations, sociodemographic predictors, and seasonal variability - Chenye Jin; Qian Yao; Yijun Zhou; Rong Shi; Yu Gao; Caifeng Wang; Ying Tian (Environmental Science and Pollution Research, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Prenatal exposure to organophosphate pesticides, maternal paraoxonase 1 genotype, and childhood neurodevelopment at 24 months of age in Shandong, China - Yiwen Wang; Yan Zhang; Lin Ji; Yijun Zhou; Rong Shi; Michihiro Kamijima; Jun Ueyama; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2020)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

The relationship between surface spectral albedo and soil moisture in an arid Gobi area - Zhenchao Li; Jiaxi Yang; Xiaoqing Gao; Ye Yu; Zhiyuan Zheng; Rong Liu; Chao Wang; Xuhong Hou; Zhigang Wei (Theoretical and Applied Climatology, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Efficiency of maternal-fetal transfer of perfluoroalkyl and polyfluoroalkyl substances - Yiwen Wang; Wenchao Han; Caifeng Wang; Yijun Zhou; Rong Shi; Eva Cecilie Bonefeld-Jørgensen; Qian Yao; Tao Yuan; Yu Gao; Jun Zhang; Ying Tian (Environmental Science and Pollution Research, 2019)

Effective inhibition of different Japanese encephalitis virus genotypes by RNA interference targeting two conserved viral gene sequences in vitro and in vivo - Lei Yuan; Xiaojuan Feng; Xuelian Gao; Yu Luo; Chaoyue Liu; Peng Liu; Guolin Yang; Hong Ren; Rong Huang; Yalan Feng; Jian Yang (Virus Genes, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Detrital apatite fission track constraints on Cenozoic tectonic evolution of the northeastern Qinghai-Tibet Plateau, China: Evidence from Cenozoic strata in Lulehe section, Northern Qaidam Basin - Ding-ding Du; Cheng-jun Zhang; Muhammad Saleem Mughal; Xiao-yu Wang; Dembele Blaise; Jun-ping Gao; Yuan Ma; Xin-rong Luo (Journal of Mountain Science, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Possible Effects of Electric Fields on a Pair of Spherical Cells - Yu Zheng; Jing Xue; Yang Gao; Lei Dong; Jun-rong Dou; Wei Ma (The Journal of Membrane Biology, 2017)

Characterization of a Gallid herpesvirus 2 strain with novel reticuloendotheliosis virus long terminal repeat inserts - Yan-ping Zhang; Ke-yan Bao; Guo-rong Sun; Hong-chao Lv; Hong-yu Cui; Yu-long Gao; Xiao-mei Wang; Chang-jun Liu (Virus Genes, 2017)

Streptomyces xiangtanensis sp. nov., isolated from a manganese-contaminated soil - Ping Mo; Yi-Zun Yu; Jia-Rong Zhao; Jian Gao (Antonie van Leeuwenhoek, 2017)

Strawberry MOTHER OF FT AND TFL1 regulates seed germination and post-germination growth through integrating GA and ABA signaling in Arabidopsis - Yang Hu; Yu-Rong Gao; Wei Wei; Kai Zhang; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Prenatal low-level mercury exposure and infant neurodevelopment at 12 months in rural northern China - Yi Hu; Limei Chen; Caifeng Wang; Yijun Zhou; Yan Zhang; Yiwen Wang; Rong Shi; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Development and evaluation of a loop-mediated isothermal amplification assay for rapid detection of bacterial blight pathogen (Xanthomonas axonopodis pv. dieffenbachiae) in anthurium - Niu Jun-hai; Gao Yue-rong; Yin Jun-mei; Leng Qing-yun; Yang Guang-sui; Wang Cun; Ren Yu (European Journal of Plant Pathology, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Reference gene selection for real-time RT-PCR normalization in rice field eel (Monopterus albus) during gonad development - Qing Hu; Wei Guo; Yu Gao; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2014)

Effects of low-voltage constant direct current on plasma biochemical profiles and gene expression levels in crucian carp Carassius carassius - Yu Gao; Dapeng Li; Xiaozhen Peng; Rong Tang (Fisheries Science, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Establishment of a Spinal Cord Injury Model in Adult Rats by an Electrocircuit-Controlled Impacting Device and its Pathological Observations - Yun Wang; Chun-feng Liu; Qi-ping Wang; Heng Gao; Han-rong Na; Ru-tong Yu (Cell Biochemistry and Biophysics, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

Manganese concentrations in maternal–infant blood and birth weight - Limei Chen; Guodong Ding; Yu Gao; Pei Wang; Rong Shi; Hong Huang; Ying Tian (Environmental Science and Pollution Research, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Short-term effect of cultivation and crop rotation systems on soil quality indicators in a coastal newly reclaimed farming area - Rong-Jiang Yao; Jing-Song Yang; Tong-Juan Zhang; Peng Gao; Shi-Peng Yu; Xiang-Ping Wang (Journal of Soils and Sediments, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

The contribution of intersubspecific hybridization to the breeding of super-high-yielding japonica rice in northeast China - Jian Sun; Di Liu; Jia-Yu Wang; Dian-Rong Ma; Liang Tang; Hong Gao; Zheng-Jin Xu; Wen-Fu Chen (Theoretical and Applied Genetics, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

LysGH15B, the SH3b Domain of Staphylococcal Phage Endolysin LysGH15, Retains High Affinity to Staphylococci - Jingmin Gu; Rong Lu; Xiaohe Liu; Wenyu Han; Liancheng Lei; Yu Gao; Honglei Zhao; Yue Li; Yuwen Diao (Current Microbiology, 2011)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Benefits of a symbiotic association with endophytic fungi are subject to water and nutrient availability in Achnatherum sibiricum - An Zhi Ren; Xia Li; Rong Han; Li Jia Yin; Mao Ying Wei; Yu Bao Gao (Plant and Soil, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Assessment of inheritance pattern and agronomic performance of transgenic rapeseed having harpinXooc-encoding hrf2 Gene - Rong Huo; Yu Wang; Ling-Li Ma; Jun-Qing Qiao; Min Shao; Xue-Wen Gao (Transgenic Research, 2010)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Saponin fraction from Astragalus membranaceus roots protects mice against polymicrobial sepsis induced by cecal ligation and puncture by inhibiting inflammation and upregulating protein C pathway - Xing-hua Gao; Xian-xiang Xu; Rong Pan; Ying Li; Yu-bin Luo; Yu-feng Xia; Kazuya Murata; Hideaki Matsuda; Yue Dai (Journal of Natural Medicines, 2009)

PEG-conjugated PAMAM Dendrimers Mediate Efficient Intramuscular Gene Expression - Rong Qi; Yu Gao; Yin Tang; Rui-Rui He; Tao-Le Liu; Yun He; Sheng Sun; Bo-Yu Li; Yang-Bing Li; George Liu (The AAPS Journal, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Akt/PKB interacts with the histone H3 methyltransferase SETDB1 and coordinates to silence gene expression - Haidong Gao; Zhigang Yu; Dongsong Bi; Liyu Jiang; Yazhou Cui; Jingzhong Sun; Rong Ma (Molecular and Cellular Biochemistry, 2007)

Dependent mechanism of Chinese prepositions processing in the brain: evidence from event-related potentials - Huan-Hai Fang; Rong-Ping Zhang; Huan-Fei Fang; Ming-Yang Gao; Min Zheng; Xiao-Yu Sun (Neuroscience Bulletin, 2007)

Mutation induced by ethylmethanesulphonate (EMS), in vitro screening for salt tolerance and plant regeneration of sweet potato (Ipomoea batatas L.) - Yu-Shi Luan; Juan Zhang; Xiao-Rong Gao; Li-Jia An (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Pharmacokinetics of three proton pump inhibitors in Chinese subjects in relation to the CYP2C19 genotype - Hai-Ling Qiao; Yu-Rong Hu; Xin Tian; Lin-Jing Jia; Na Gao; Li-Rong Zhang; Yu-Zhong Guo (European Journal of Clinical Pharmacology, 2006)

Environmental evolution of ordos desert in china since 1.1Ma B.P. as indicated by Yulin stratigraphical section and its grain-size analysis results - Bao-sheng Li; Shang-yu Gao; Guang-rong Dong; He-ling Jin (Chinese Geographical Science, 2005)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)